Strategically managing information security risks - Ray, Amy (Henry Stewart Talks, 2011)
Cornerstones of security strategy, Current business environment, Business growth vs. Information Security, Risky business activities, Teleworking, Malicious attacks, Malware, Spam and phishing, Denial-of-service attacks, Implications, Why we can't get ahead on security, The changing security landscape, Security strategy, Security architecture, Security technology, Return on Security Investment